Study to Analyze the Dosimetric Characteristics of High Dose Rate Flattening Filter-Free Beam from different Linear Accelerators - D, Palanivelu; D, Khanna; P, Mohandass; M, Thirumal; R J, Raghul; S, Venugopal (Asian Pacific Journal of Cancer Biology, 2026)
Background: Numerous radiation-generating devices produce flattening filter-free (FFF) beams for treating cancer patients clinically, while all those machines produce FFF beams, they differ in their treatment head, collimation system, Multi leaf collimator (MLC) configurations, MLC speed, gantry speed, and dose rate. Objective of this study was to compare dosimetric characteristics of FFF beams used in different linear accelerators (Linacs) from multiple radiotherapy centres. Methods: Dosimetric data for 6MV FFF and 10MV FFF beams from Elekta Versa HD™ (EVH1 & EVH2), Varian TrueBeam™ (VT1 & VT2), and 6MV FFF from Varian Halcyon™ (VH1 & VH2) were analyzed. This study compared different dosimetric parameters included depth of maximum dose (Dmax), beam quality index, percentage depth dose (PDD), beam profiles, penumbra, off-axis ratio, percentage surface dose (PSD), head leakage, and multi-leaf collimator (MLC) leakage. Results: The VH showed significantly lower MLC transmission (0.007–0.03%) compared to VT (1.21–1.23%) and EVH (0.23–0.34%). PSD for a 30×30 cm² field was lower in EVH (37.1–38.4%) than VT (49.3–51.1%) but higher for a 28×28 cm² field in VH (66.2–69.1%). Head leakage showed no major differences, with values in the patient plane of 0.004–0.014% (EVH), 0.005-0.03% (VT), and 0.012–0.10% (VH); and other than patient plane of 0.02–0.10% (EVH), 0.007% (VT), and 0.012–0.209% (VH). Penumbra was slightly lesser in VH (8.9 mm) than VT (9.5 mm) and EVH (9.8 mm). VH exhibited excellent MLC shielding and a narrower penumbra, ensuring better conformity and minimal leakage. EVH had lower PSD, offering improved skin sparing. VT showed higher MLC transmission, indicating slightly higher out-of-field dose. Head leakage was lesser for all machines, confirming effective shielding design. Conclusion: Overall analysis shows clear performance variations among the evaluated linac platforms. EVH exhibited a higher energy spectrum, while VH and VT demonstrated slightly lower values. VH showed the lowest MLC leakage. Comprehensive dosimetric comparisons are essential when commissioning FFF linacs. Machine specific parameter must be assessed and optimized for clinical needs. Such evaluations are key for advanced radiotherapy quality. Centres should consider these technical details in commissioning and deployment.